Letter: be careful of gastrointestinal CMV infection in adverse event from ICIs therapy in solid tumours—Authors' reply. Issue 8 (23rd March 2023) - Dahl, Emilie; Abed, Osama; Agnholt, Jørgen; Bjerrum, Jacob; Dige, Anders; Kjeldsen, Jens; Svane, Inge; Donia, Marco; Seidelin, Jakob
LINKED CONTENT: This article is linked to Dahl et al papers. To view these articles, visit https://doi.org/10.1111/apt.17201 and https://doi.org/10.1111/apt.17416